Network of protein interactions within the Drosophila inner kinetochore. Issue 2 (February 2016) - Richter, Magdalena M.; Poznanski, Jaroslaw; Zdziarska, Anna; Czarnocki-Cieciura, Mariusz; Lipinszki, Zoltan; Dadlez, Michal; Glover, David M.; Przewloka, Marcin R.
Abstract : The kinetochore provides a physical connection between microtubules and the centromeric regions of chromosomes that is critical for their equitable segregation. The trimeric Mis12 sub-complex of the Drosophila kinetochore binds to the mitotic centromere using CENP-C as a platform. However, knowledge of the precise connections between Mis12 complex components and CENP-C has remained elusive despite the fundamental importance of this part of the cell division machinery. Here, we employ hydrogen–deuterium exchange coupled with mass spectrometry to reveal that Mis12 and Nnf1 form a dimer maintained by interacting coiled-coil (CC) domains within the carboxy-terminal parts of both proteins. Adjacent to these interacting CCs is a carboxy-terminal domain that also interacts with Nsl1. The amino-terminal parts of Mis12 and Nnf1 form a CENP-C-binding surface, which docks the complex and thus the entire kinetochore to mitotic centromeres. Mutational analysis confirms these precise interactions are critical for both structure and function of the complex. Thus, we conclude the organization of the Mis12–Nnf1 dimer confers upon the Mis12 complex a bipolar, elongated structure that is critical for kinetochore function.